Age and the means of bypassing stasis influence the intrinsic subtype of immortalized human mammary epithelial cells - Lee, Jonathan K.; Garbe, James C.; Vrba, Lukas; Miyano, Masaru; Futscher, Bernard W.; Stampfer, Martha R.; LaBarge, Mark A. (Frontiers in Cell and Developmental Biology, 2015)
Based on molecular features, breast cancers are grouped into intrinsic subtypes that have different prognoses and therapeutic response profiles. With increasing age, breast cancer incidence increases, with hormone receptor-positive and other luminal-like subtype tumors comprising a majority of cases. It is not known at what stage of tumor progression subtype specification occurs, nor how the process of aging affects the intrinsic subtype. We examined subtype markers in immortalized human mammary epithelial cell lines established following exposure of primary cultured cell strains to a two-step immortalization protocol that targets the two main barriers to immortality: stasis (stress-associated senescence) and replicative senescence. Cell lines derived from epithelial cells obtained from non-tumorous pre- and post-menopausal breast surgery tissues were compared. Additionally, comparisons were made between lines generated using two different genetic interventions to bypass stasis: transduction of either an shRNA that down-regulated p16INK4A, or overexpressed constitutive active cyclin D1/CDK2. In all cases, the replicative senescence barrier was bypassed by transduction of c-Myc. Cells from all resulting immortal lines exhibited normal karyotypes. Immunofluorescence, flow cytometry, and gene expression analyses of lineage-specific markers were used to categorize the intrinsic subtypes of the immortalized lines. Bypassing stasis with p16 shRNA in young strains generated cell lines that were invariably basal-like, but the lines examined from older strains exhibited some luminal features such as keratin 19 and estrogen receptor expression. Overexpression of cyclin D1/CDK2 resulted in keratin 19 positive, luminal-like cell lines from both young and old strains, and the lines examined from older strains exhibited estrogen receptor expression. Thus age and the method of bypassing stasis are independent determinants of subtype in immortalized human mammary epithelial cells.